PENGARUH KINERJA KEUANGAN, STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN MELALUI KEBIJAKAN DIVIDEN INDUSTRI JASA SEKTOR KEUANGAN TBK PERIODE 2020 - 2022 - Septian, Nanda Ayu (Jurnal Manajerial Bisnis, 2024)
This research aims to test and analyze the significant influence of financial performance, capital structure and company size on company value through the dividend policy of the Tbk financial services industry for the period 2020 - 2022. This research uses an explanatory research type of research using a quantitative approach. The sampling technique used the purposive sampling method, a sample of 21 financial sector service industries was obtained from a total population of 51 financial sector service industries. The type of data in this research is secondary data. Data obtained from the official website of the Indonesia Stock Exchange in the form of annual financial reports from the financial sector services industry for the period 2020 - 2022. Data analysis was carried out using descriptive statistics with the SmartPLS tool. Based on the results of data analysis, it shows that financial performance, company size and dividend policy have a positive and significant influence on company value, capital structure has no effect on company value. Financial performance, capital structure and company size have a positive influence on dividend policy. Financial performance, capital structure and company size have a positive influence on company value through dividend policy.